ANALISIS DAMPAK NPL, CKPN, LDR DAN SUKU BUNGA KREDIT TERHADAP PENYALURAN KREDIT PERBANKAN PADA MASA PANDEMI COVID-19 - Lesia Fatma Ginoga; Asty Khairi Inayah Syahwani (Politeknik Negeri Jakarta, 2022)
ABSTRACT During the Covid-19 Pandemic, the banking sector experienced slow credit growth, this was due to the weakening economy and sluggish public purchasing power. At the beginning of the Covid-19 pandemic, the Basic Loan Interest Rate (SBDK) did not experience a significant decline, Banks also had to be more careful in lending to avoid Non-Performing Loans (NPLs). Credit reserves or Allowance for Impairment Losses (CKPN) must also be reserved for all credit categories in accordance with PSAK 71. In the midst of the COVID-19 pandemic, Banks must also maintain a Loan to Deposit Ratio (LDR) in the range of 75% - 80% in order to continue to fulfill one of the health elements of the bank. This study aims to determine the effect of Non-Performing Loans (NPL), Allowance for Impairment Losses (CKPN), Basic Credit Interest Rates (SBDK), and Loan to Deposit Ratio (LDR) on lending. The research data is secondary data, namely the Quarterly Financial Statements from March 2020-March 2021. The analytical method used is panel data regression analysis. The results showed that CKPN and LDR had a significant effect on lending while NPL and SBDK had no significant effect on lending. Keywords: Covid19 pandemic, SBDK, LDR, CKPN